Investigating the Independent Curriculum in English Language Learning at MA Raudlatul Ulum Putri - Robiatul Adawiyah; Budik Kusworo (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study is to find out the implementation of Merdeka Curriculum in English learning at MA Raudlatul Ulum Putri, with a focus on its effect on students' creativity, interest, participation, and self-confidence. This study uses a descriptive qualitative method with data collection through observation, interviews with English teachers, several grade XI students, and the deputy head of the madrasah for curriculum, and is supported by documentation. The results showed that the Independent Curriculum is able to increase students' creativity through project-based tasks such as making posters, storytelling, and presentations. Contextual and interactive learning materials, such as the use of songs and discussion topics that are close to their lives, have succeeded in increasing interest and motivation to learn. The conducive classroom atmosphere also encourages students' active participation because they feel safe to express their opinions. Students become more confident and engaged in learning, which contributes positively to their overall academic experience and social interaction. In addition, the curriculum promotes collaboration among students, allowing them to learn from one another through group activities and peer discussions. Teachers are given greater flexibility to design learning activities tailored to students' needs, while the deputy principal for curriculum plays an important role in providing support and supervision during the curriculum transition. The study concludes that the Independent Curriculum fosters a more contextualized, participatory, and empowering learning environment. It is recommended that continuous professional development for teachers and strong managerial support be maintained to ensure sustainable curriculum implementation.